Samuel's baby - Elkin, Mark (Tricycle Press, 2010)
Samuel announces during show-and-tell that he is having a baby and soon his kindergarten classmates are expecting everything from twins to puppies, but while Samuel teaches them how to hold and diaper a newborn, he has some qualms about becoming a big brother.